The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3171/2015.3.peds14649
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of adolescent idiopathic scoliosis in the United States from 1997 to 2012: an analysis of 20, 346 patients

Abstract: OBJECT Adolescent idiopathic scoliosis (AIS) can cause substantial morbidity and may require surgical intervention. In this study, the authors aimed to evaluate US trends in operative AIS as well as patient comorbidities, operative approach, in-hospital complications, hospital length of stay (LOS), and hospital charges in the US for the period from 1997 to 2012. METHODS Patients with AIS (ICD-9-CM diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 32 publications
(25 reference statements)
3
64
0
3
Order By: Relevance
“…These results mirror findings from other large population-based research demonstrating significant reductions in hospital LOS [7,8,17,20]. Vigneswaran et al in a study of surgical outcomes in individuals with idiopathic scoliosis, reported a decrease in average hospital LOS from 6.5 days in 1997 to 5.6 days in 2012 [8], which does not seem to be associated with higher complication rates [21].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These results mirror findings from other large population-based research demonstrating significant reductions in hospital LOS [7,8,17,20]. Vigneswaran et al in a study of surgical outcomes in individuals with idiopathic scoliosis, reported a decrease in average hospital LOS from 6.5 days in 1997 to 5.6 days in 2012 [8], which does not seem to be associated with higher complication rates [21].…”
Section: Discussionsupporting
confidence: 80%
“…This trend was also found in the US among adolescents undergoing surgery for scoliosis [7,8]. Vigneswaran et al in a study of 20,346 adolescents with scoliosis aged 0-12 years, found posterior fusions increased from 63.4% in 1997 to 94.1% in 2012 [8].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Bleeding in major surgery often necessitates the transfusion of allogeneic red blood cells (RBCs), which is associated with an increased risk of infection and alloimmunization as well as hemolytic, febrile, and allergic reactions . In patients with adolescent idiopathic scoliosis (AIS), surgical treatment involves a posterior approach with multisegmental pedicle screw fixation . Although this procedure is generally considered safe with few surgical complications, there are considerable variations in fusion length, surgical time, and the extent of soft‐tissue exposure .…”
Section: Objectivementioning
confidence: 99%